Plantation Politics and Neoliberal Racism in Higher Education: A Framework for Reconstructing Anti-Racist Institutions. Issue 14 (November 2018) - Squire, Dian; Williams, Bianca C.; Tuitt, Frank
Overcoming the deeply embedded anti-Black racism and colonial heritage of North America is an ongoing project. Scholars have yet to explicate fully the ways that racism and colonialism are foundational to the construction of institutions of higher education. Plantation politics provides the opportunity to reveal parallel organizational and cultural norms between contemporary higher education institutions and slave plantations. To better explore the applicability of this theory, the authors share an example of the parallel between slave plantations and contemporary universities called "The Oxymoronic Social Existence of Whites (or Neoliberalism as the New Slave Code)" and its implications for campus practice toward racial liberation. The authors argue that the institutional logics of colonialism and imperialism— which were essential to the establishment of this country and led to the creation of plantations and the enslavement of Black bodies—exists within higher education institutions today.